A legacy that challenges science: Rectifying vandalistic practices in Orthoptera taxonomy - Ciplak, Battal; Uluar, Onur; Chobanov, Dragan P. (Zootaxa, 2026)
Knowledge can arise from various approaches, yet only that generated through empirical processes (objective, systematic, and empirical evidence-based) constitutes true scientific knowledge. Taxonomy, as the discipline that develops theory and principles of organismal classification, must function within these scientific standards. When detached from them, taxonomy loses both its function and its credibility. Practices that disregard empirical evidence and distort previously established data have been identified as taxonomic vandalism in the literature. As a scientific enterprise, taxonomy progresses through proposing hypotheses and testing them empirically. Every taxonomic act implies a hypothesis whose validity can only be demonstrated by data-based evaluation. Acts performed without such testing fall outside the scientific norms and represent vandalistic behaviour. Correcting nomenclatural acts derived from such approaches is therefore essential to maintaining the integrity of taxonomic knowledge. In this study, a genus, a subgenus and several species within Tettigoniidae (Orthoptera) that were invalidated by subjective reasoning and unsupported claims are reinstated as valid taxa. Based on empirical evidence, the following taxa are restored to valid status: Bolua balikesirensis Uluar & Çıplak, 2022 sp. rev., B. bursaensis Uluar & Çıplak, 2022 sp. rev.; Anterastes boreoanatoliensis Çıplak & Uluar, 2023 sp. rev., A. muratdagensis Çıplak & Uluar, 2023 sp. rev., A. kizkayasiensis Çıplak & Uluar, 2023 sp. rev., A. ucari Çıplak, 2004 sp. rev.; Psorodonotus rize Kaya & Çıplak, 2014 sp. rev., P. giresun Kaya & Çıplak, 2014 sp. rev., P. inermis Ramme, 1951 sp. rev.; Eupholidoptera femorata Çıplak, 1999 sp. rev., E. helina Çıplak, 2009 sp. rev.; Hamatopoecilimon Heller, 2011 subgen.rev., and the genus Aparapholidoptera Çıplak, 2021 gen. rev., with revalidation of the following combinations A. distincta (Uvarov, 1921) comb. rev., A. karabagi (Demirsoy, 1974) comb. rev., A. kosswigi (Karabağ, 1950) comb. rev., and A. ziganensis (Karabağ, 1964) comb. rev.. Finally, the paper outlines principles and recommendations aimed at preventing similar non-scientific practices in the future.